Thirdhand smoke beliefs, exposure status and associated factors among young people in China: A cross-sectional study - Qinyi Guan; Jianrong Mai; Kaisheng Teng; Zhihong Liu; Lina Lin; Ling Zhou; Tingfen Huang; Xiaoyu Tan; Xinying Sun (Tobacco Induced Diseases, 2023)
Introduction Thirdhand smoke is an emerging threat to global public health. There is no research on young people's exposure to thirdhand smoke in China. This study aims to investigate the exposure status and beliefs of thirdhand smoke among young Chinese people and provide a reference for policy regarding thirdhand smoke.